The written turn of Mapuche historiography: alphabet and archives at the borderlands. A state of the art (Quinto Sol, 2019)
This work traces an overview of recent advances in the knowledge about the appropriation and uses of writing by the indigenous population of Pampa, Patagonia and Araucanía between the 18th and the 21st centuries. The contributions to the identification and analysis of diverse corpus produced by indigenous people are stressed, since they allowed to achieve a more complex knowledge on the political relations between the indigenous leaders and state agents, highlighting the appropriation of the writing as a tool in the frontier diplomacy and as an expression of the commercial, parental and military networks that connected these regions. Also, this text introduces the papers in this special issue. The question about the formats, specificity and features of indigenous archives is the axis for this integrating reading of the articles to be presented.
Keywords: archives; indigenous peoples; writing; corpus